Hak Waris Bagi Anak Hasil Zina dalam Kajian Ilmu Matematika dan Hukum Islam - Faizatul Fil Ula; Risma Meliyana; Rohmatul Ilahiyah; Mohammad Tohir (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Mawaris in the fiqh discourse is commonly referred to as the science of faraidh. Faraidh discusses the issue of inheritance rights (tirkah) to the heirs of the owner who has passed away. One of the problems related to inheritance law is the inheritance rights for a child resulting from adultery and its distribution mathematically. Hence, this study aims to describe the role of mathematics in the distribution of inheritance rights for a child resulting from adultery based on the Islamic law. The research method used is a literature study, documentation, and focused discussion. The subjects in this study are inheritance and Islamic law, while the objects are children of adultery. The results show that: (1) the ability to perform basic operations and mathematical fraction operations plays an active role in the distribution of inheritance rights for a child resulting from adultery; (2) choosing the right problem-solving strategy is very helpful in distributing inheritance rights for a child resulting from adultery; (3) the role of mathematics in the distribution of inheritance rights for a child resulting from adultery can minimize the controversy that often occurs in society; (4) Islamic law has determined that a child resulting from adultery does not fester on the part of the biological father, but on the side of the biological mother even though the one who married the biological mother is the biological father; (5) a child resulting from adultery only gets inherited property from the biological mother, while from the biological father's side, that child only gets obligatory assets; and (6) the decendant’s status falls on the biological father if the child has been born for more than 6 months after the marriage contract between the parents